2002
DOI: 10.1002/humu.10047
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 33 polymorphisms in the adipocyte-derived leucine aminopeptidase (ALAP) gene and possible association with hypertension

Abstract: Adipocyte-derived leucine aminopeptidase (ALAP) inactivates angiotensin II and/or generates bradykinin in the kidney, suggesting a possible role for ALAP in the regulation of blood pressure. We considered the hypothesis that genomic variants of the ALAP gene are associated with hypertension or individual variations in blood pressure. We screened for mutations in the ALAP gene in 48 unrelated Japanese individuals and identified 33 polymorphisms including 15 novel polymorphisms. We then performed a two-stage ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
85
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 13 publications
1
85
0
2
Order By: Relevance
“…5) and the resulting specificity for 9-to 16-residue substrates, like its subcellular localization and regulation by IFN-␥, must have evolved to facilitate immune surveillance. Much, however, remains to be learned about its precise role in processing different types of epitopes, the possible immunological significance of the human polymorphisms in ERAP1 (46), and the structural basis for its molecular ruler mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…5) and the resulting specificity for 9-to 16-residue substrates, like its subcellular localization and regulation by IFN-␥, must have evolved to facilitate immune surveillance. Much, however, remains to be learned about its precise role in processing different types of epitopes, the possible immunological significance of the human polymorphisms in ERAP1 (46), and the structural basis for its molecular ruler mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The unique localization of the enzymes may suggest the biological functions of the oxytocinase subfamily to be strictly regulated. Indeed, it is getting evident that the enzymes belonging to this subfamily play important roles in the maintenance of homeostasis such as blood pressure regulation, angiogenesis, and maintenance of memory (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that A-LAP, which cleaves angiotensin II and III and kallidin, regulates blood pressure (24,46), it is tempting to speculate that L-RAP also plays a role in the regulation of blood pressure by inactivating angiotensin III and generating bradykinin. Putative ER retention machinery may play a role in the biological function of substrate peptides by regulating the secretion of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, by screening for polymorphisms in the human ERAP1 gene, Yamamoto et al (13) identified an association of K528R variant enzyme with essential hypertension. Indeed, K528R mutant ERAP1 had less enzymatic activity than the wild type (14); therefore, it is conceivable that although ERAP1 is usually retained in the ER, 2 the enzyme is secreted into the extracellular milieu in response to specific stimuli and in turn regulates blood pressure by processing peptide substrates in blood vessels.…”
mentioning
confidence: 99%